2022
DOI: 10.1101/2022.04.05.487195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unaltered T cell responses to common antigens in individuals with Parkinson’s disease

Abstract: Background and ObjectivesParkinson’s disease (PD) is associated with a heightened inflammatory state, including activated T cells. However, it is unclear whether these PD T cell responses are antigen specific or more indicative of generalized hyperresponsiveness. Our objective was to measure and compare antigen-specific T cell responses directed towards antigens derived from commonly encountered human pathogens/vaccines in patients with PD and age-matched healthy controls (HC).MethodsPeripheral blood mononucle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Several epidemiological studies have suggested that pertussis may increase the risk of PD (de Pedro-Cuesta et al, 1996;Vlajinac et al, 2013). Further research has indicated that there is no direct relationship between PD and pertussis vaccination or immunoglobulin against pertussis, suggesting that the association is not simply a result of immunological responses to the bacteria (Fiszer et al, 2004;Williams et al, 2023). On the other hand, studies on atherosclerosis have shown that oxLDL can inhibit the endothelium-dependent relaxation of arteries via pertussis toxinsensitive G proteins (Shimokawa et al, 1991;Jing et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have suggested that pertussis may increase the risk of PD (de Pedro-Cuesta et al, 1996;Vlajinac et al, 2013). Further research has indicated that there is no direct relationship between PD and pertussis vaccination or immunoglobulin against pertussis, suggesting that the association is not simply a result of immunological responses to the bacteria (Fiszer et al, 2004;Williams et al, 2023). On the other hand, studies on atherosclerosis have shown that oxLDL can inhibit the endothelium-dependent relaxation of arteries via pertussis toxinsensitive G proteins (Shimokawa et al, 1991;Jing et al, 1999).…”
Section: Discussionmentioning
confidence: 99%